The Contribution of the Triage Nurse in the Optimisation of Door-to-Computed-Tomography Time in Stroke - Raquel Antunes; Cristina Costeira; Joana Pereira Sousa; Cátia Santos (MDPI AG, 2024)
A stroke is a time-sensitive emergency, so diagnosing and treating the victim promptly is extremely important. Therefore, the purpose of this study was to identify the influence of the Stroke Code Protocol's activation on the door-to-computed-tomography (door-to-CT) time and determine whether factors such as previous Modified Rankin Scale (mRS), age, and gender influence its activation. A retrospective study was conducted in a Medical-Surgical Emergency Department in the centre of Portugal from 1 January 2021 to 31 December 2022. The sample was selected according to the diagnosis assigned at the time of clinical discharge from the Emergency Department and the Stroke Code Protocol activation criteria. It was observed that 113 (50%) suspected stroke victims who met the activation criteria for the Stroke Code Protocol did not have the protocol activated, which had a highly significant influence (p < 0.001) on door-to-CT time. It was determined that activation at triage has an average door-to-CT time of 35 ± 18 min, post-triage activation has an average door-to-CT time of 38 ± 26 min, and non-activation has an average door-to-CT time of 1 h 04 ± 45 min. The need to implement an institutional protocol for activating the Stroke Code Protocol and provide specialised training for the multidisciplinary team is reiterated.